Erlotinib Induced Fatal Interstitial Lung Disease: An Underreported Toxicity (Global Journal of Medical Research, 2016)
Lung cancer is the leading cause of cancer-related mortality around the world, with 85% of cases identified as non-small-cell lung cancer (NSCLC). Adenocarcinoma is the most common histologic subtype in the US and accounts for more than 50% of all NSCLC. Activating mutations in the epidermal growth factor receptor (EGFR) tyrosine kinase are found in approximately 15% of NSCLC adenocarcinoma in the US (and up to 62% in Asia) and is more common in nonsmokers. The presence of such a mutation is associated with a more favorable prognosis and predicts for sensitivity to EGFR tyrosine kinase inhibitors (TKIs) such as erlotinib, gefitinib, and afatinib. Treatment is well tolerated, with mild common adverse side effects of skin rash and diarrhea. However, increased experience with the use of these drugs has led to reports of rare serious adverse effects such as interstitial lung disease.
Keywords: erlotinib; Interstitial lung disease; Rare Side effects; chemotherapy